Theoretical insights into selective electrochemical conversion of carbon dioxide - Lee, Chan Woo; Kim, Chanyeon; Min, Byoung Koun (Springer | Korea Nano Technology Research Society, 2019)
Electrochemical conversion of CO2 and water to valuable chemicals and fuels is one of the promising alternatives to replace fossil fuel-based processes in realizing a carbon-neutral cycle. For practical application of such technologies, suppressing hydrogen evolution reaction and facilitating the activation of stable CO2 molecules still remain major challenges. Furthermore, high production selectivity toward high-value chemicals such as ethylene, ethanol, and even n-propanol is also not easy task to achieve. To settle these challenges, deeper understanding on underlying basis of reactions such as how intermediate binding affinities can be engineered at catalyst surfaces need to be discussed. In this review, we briefly outline recent strategies to modulate the binding energies of key intermediates for CO2 reduction reactions, based on theoretical insights from density functional theory calculation studies. In addition, important design principles of catalysts and electrolytes are also provided, which would contribute to the development of highly active catalysts for CO2 electroreduction.